Guided wave scattering at a delamination in a quasi-isotropic composite laminate: Experiment and simulation. (1st November 2021) - Hervin, F.; Maio, L.; Fromme, P.
Highlights: Guided ultrasonic wavefield measurements performed on quasi-isotropic CFRP laminate. Scattering at artificial, ellipse delamination, located at an asymmetric depth. Wave trapping on top of delamination and forward scattered wave verified. Numerical, Finite Element simulations validated from experiments. Parameter study of guided wave scattering at different delamination shape and depth. Abstract: Carbon fibre composite laminates are increasingly being used for aerospace structures due to their low weight and improved mechanical performance. Impact damage can cause delaminations below the visible surface of the structure due to limited interlaminar strength. Guided ultrasonic waves can detect and characterize delaminations in composite laminates. The scattering of the A0 Lamb wave mode at an artificial delamination, located at an asymmetric depth in a quasi-isotropic laminate, was investigated. Full field non-contact laser measurements were used to visualise wave trapping and scattered waves. A three-dimensional finite element model was developed and validated against the experiments. The influence of delamination shape and depth on guided wave scattering were studied. Small variations in delamination shape significantly affected the interference pattern on top of the delamination, but had limited effect on the scattered wave outside the delamination. Delamination depth was found to strongly influence the angular direction and amplitude of scattered waves. Implications for structural health monitoring were discussed.